How to Detect and Prevent Errors in Computer-Supported Statistical Analysis: An Example - Haux, R. (Methods of Information in Medicine, 1983)
In statistical analysis systems data are stored in a database, and procedures or analysis methods, respectively, are stored in a method base. As will be shown in the present article, even in the case of a simple statistical test the detection of faulty data turns out to be deficient in weill-known statistical analysis systems like BMDP, SAS and SPSS. Suggestions are made to program methods and to design statistical analysis systems in such a way that careful error detection is possible to provide the user with more reliable results.
Keywords: Statistical Analysis Systems; Error Detection; WILCOXON-MANN-WHITNEY Test; Semantic Integrity Constraints; Statistical Quality; Statistical Computing; BMDP; SAS; SPSS